GECİKMİŞ ARTERYEL EMBOLİLER: EMBOLEKTOMİ YAPILMALI MIDIR? - İRİZ, Erkan and KALAYCIOĞLU, Sedat and SİNCİ, Volkan (Cerrahpaşa Medical Journal, 2014)
Background and Design.-We studied the effectivity of delayed embolectomy in late applied patients. Meanwhile, we reviewed the literature. Eight patients, who had embolism symptoms more than 15 days and had late embolectomy between September 2002 and April 2004, were included in the study. The seven patients were male and one patient was female with average of age 71.3 ± 9.1. The patients applied to hospital 23.3±7.6 days after the beginning of symptoms (Between 16-38 days). The patients have been followed for 14.0±8.3. All patients operated at the day they applied our hospital. The obstruction levels were the distal of superficial femoral artery in 6 patients, iliac level in 1 patient and in the upper extremity in 1 case. 7 patients had hyperlipidemia, 5 patients had hypertension and 4 patients had diabetes mellitus as additional diseases. All the operations performed with local anesthesia and standard insicions. In all patients 7F Fogarty catheter were used for proximal embolectomy and 4F for distal. The organized thrombus was extracted from all patients. Distal and proximal portion of the arteriotomy were washed up with heparine 5000 Ü and bicarbonate solutions. Results.- After embolectomy, all patients had distal arterial pulsation with palpation. One patient was required re-operation in the first month. Of four patients had finger amputations and there was no need for higher level amputation. In the three patients reversible drop foot occurred. Conclusion.- Late embolectomy increases the blood perfusion and decreases the level of amputation of the extremity. We believe that a chance must be given, even for delayed cases.